International Law Milestones Throughout History: Forming the Idea of Modern Sovereignty - Riadhotul Muamalah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This paper examines the evolution of international law from its early foundations to its contemporary form. Starting with the basic legal principles, it highlights significant milestones, such as the Peace of Westphalia in 1648, which established the concept of state sovereignty. The study also explores the contributions of Hugo Grotius, who is often regarded as the